Implementasi Kebijakan Program Relawan Demokrasi oleh KPU Kota Padang pada Pilkada 2018 - Kurnia Hariyanto; Al Rafni (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2019)
The number of voters in the elections post reform tends to decline. The reality has made the General Election Commission (KPU) take the policy of democracy Volunteers (relationships) that the management is located in the city level or districts. The main objective of the volunteer democracy policy is increasing voters participation. In Padang City, the Program policy is assessed successfully. This can be seen from voters ' participation in the 2013 election which is only about 52%, declining from the local 2008 elections where the community participation rate of Padang is around 56% and then at the election 2018 where there is a policy of volunteer democracy level Community participation increased by 12% with a participatory rate of 64%. It can be scientifically researched about how the implementation of the program of Democratic volunteers by the KPU in Padang city elections 2018 if viewed from the factors of success. The research method uses a qualitative descriptive approach. The results of the research gained that the implementation of the policy of Democratic Volunteer Program in KPU in Padang city elections there are factors of success such as effective communication, the resources of adequate democratic volunteers, even though the budget is limited, Disposition, where the volunteers of democracy have a strong commitment to run the program, and the bureaucracy structure, KPU has operational standards and a clear principal task. The purpose of the study was as one of the evaluations in the policy of KPU to increase voters participation in the elections.